Regional Human Rights Mechanism and Civil Society Advocacies: A Transformation of Regional and Civil Society - Oga, Toru (Malaysian Journal of International Relations, 2016)
This paper focuses on the dynamics of civil society that the Association of Southeast Asian Nations (ASEAN) recently has activated at regional level by examining regional-level civil society organisations and networks non-governmental organisations (NGOs), looking at the Law Association for Asia and the Pacific (LAWASIA) and the Asian Forum for Human Rights and Development (FORUM-ASIA). The paper also uncovers how ASEAN has established, maintained, and changed the concept of civil society and human rights. In addition, the paper investigates the relationship between regionalism and the institutionalisation of human rights mechanisms. Discourses on civil society and human rights in ASEAN have been associated closely with political discourses, including regionalism and communitarianism; and the normative discourses in Asian civil society have unfolded, more or less, with the acceptance of these developments. While examining the human rights discourses in Southeast Asia, the paper explores the dynamics of Asian civil society and human rights that might differ from western NGO’s practices.